Fabrication research on the sandwich layered cathode electrode for a triode field emission display prototype - 李玉魁 李晓荃 刘兴辉 卢文科 曾凡光 (Journal of semiconductors, 2013)
Based on an effective screen-printing process,a novel sandwich layered cathode electrode was developed on a cathode faceplate.The ZnO electrode was sandwiched between an indium tin oxide（ITO） electrode layer and a silver electrode layer,and the carbon nanotube was prepared directly on the exposed ITO electrode layer surface.The cathode potential could be conducted to the carbon nanotube with the sandwich layered cathode electrode.Using the carbon nanotube as a field emitter,a triode field emission display prototype with a sandwich layered cathode electrode was fabricated,which possessed a better field emission characteristic,higher luminous brightness and better emission image luminance uniformity.The turn-on electric field was 1.88 V/μm and the measured maximum field emission current was 2273.6μA at 3.19 V/μm.By the method of adjusting the field emission current,the electron-emitting uniform capacity of the carbon nanotube cold cathode could be modified, and the emission image luminance uniformity and the emission current stability of triode field emission display prototype was also be improved significantly.The emission current fluctuation of the sandwich layered cathode electrode type field emission display was less than 1.1%.Furthermore,the total manufacture cost of the triode field emission display prototype was low.